KEADILAN TERBELAH: KONTESTASI MAZHAB DALAM IMPLEMENTASI HUKUM KELUARGA KUWAIT - Ranta Adsa; Halum Musthfa (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2026)
This article critically examines the implementation of Islamic family law in the Kuwaiti judicial system, highlighting the impact of sectarian contestation on substantive justice in judicial practice. Kuwait adheres to a dualistic family law system that separates jurisdiction between the Sunni and Shia communities, each with its own courts and different fiqh references. Codification through the Qanun al-Ahwal al-Syakhsiyyah of 1984 became the legal basis that accommodates various schools of thought, particularly Maliki, Hanbali, Shafi'i, and Ja'fari. This study uses a normative juridical approach with jurisprudential analysis of family court decisions related to divorce and ḥaḍānah (child custody) cases. Analysis of judicial practice shows that differences in doctrinal interpretation and legal procedures between schools of thought have a direct impact on variations in court decisions and unequal treatment of litigants, especially women. In divorce cases, women face different burdens of proof and legal consequences depending on their madhhab affiliation, while in child custody cases, differences in the age limit for ḥaḍānah between the Sunni and Shia madhhabs result in inconsistent rulings in cases with comparable factual circumstances. These findings indicate that Kuwait's family law system normatively accommodates fiqh plurality, but in practice gives rise to the phenomenon of “divided justice,” where legal outcomes are determined more by madhhab affiliation than by universal principles of substantive justice. Amidst the process of family law reform and Kuwait's commitment to international instruments such as CEDAW, this study recommends strengthening standards for the protection of rights and equality across schools of thought in order to realize a more just and harmonious system of family law pluralism. Keywords: Islamic Family Law, Kuwait, Divorce, Child Custody